Chad : Staff Report for the 2019 Article IV Consultation, Fourth Review under the Extended Credit Facility Arrangement, Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses Chad's 2019 Article IV Consultation, Fourth Review Under the Extended Credit Facility (ECF) Arrangement, Request for Modification of Performance Criteria, and Financing Assurances Review. Article IV discussions focused on policy priorities to deal with legacies from the crisis and the longstanding structural weaknesses. Reducing government domestic debt and domestic arrears would address key impediments to growth that persist from the crisis. Sustained efforts are needed to increase non-oil revenues, improve the efficiency and quality of public spending, and reduce the vulnerability of the fiscal position to oil price fluctuations. Performance under the ECF-supported program has been broadly satisfactory with continued improvement in the fiscal position and progress in implementing structural reforms in spite recent delays. Overall economic activity strengthened in 2018; however, further reform efforts are needed to support the recovery in the non-oil sector and improve social conditions. Chad's program is supported by the implementation of policies and reforms by the regional institutions which are critical to its success.